Peranan Audit Internal Untuk Menunjang Efektivitas Pengendalian Internal Persediaan Barang Dagang Pada PT Intan Pariwara Branch Office Metro - Nugraheni, Septiana Ayu; Nusantoro, Jawoto; Hendri, Nedi (Expensive: Jurnal Akuntansi dan Keuangan, 2022)
This study aimed to determine the role of internal audits in supporting the effectiveness of internal inventory control at PT. Intan Pariwara Branch Office, Metro. The method used in this research is qualitative with a descriptive approach. The data subject is the administration section and the Warehouse section. Data obtained by researchers through interviews and questionnaires distributed directly to research subjects. Data analysis used the miles method: data collection, data reduction, data presentation and drawing conclusions. This study's conclusion explains that the internal audit's role in inventory control has not carried out internal audit activities under good fieldwork standards: not fully implementing audit planning, program auditing, and audit procedures. And inventory control is not adequate. The completeness of invoices evidences this for issuing goods and receiving goods that are not arranged and stored properly so that it impacts stock.